2020
DOI: 10.3390/buildings10070118
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Thermal and Humidity Conditions in a Historic Wooden Building in Southern Poland

Abstract: This article presents experimental research on hygrothermal conditions in a historic wooden church in southern Poland. The scope of the research included the continuous monitoring of temperature and relative humidity in several measuring plots in different areas inside and outside of the church. We also continuously monitored the number of people attending services. This study presents a detailed analysis of the development of heat and humidity conditions within the church. A model of the object was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Chmiel et al [ 21 ] investigate bacterial and fungal aerosols in ten historical attractions from Kraków (churches, crypts, museums and libraries). Research conducted by Nawalany et al [ 22 ], Stanaszek-Tomal [ 23 ] and Mang et al [ 24 ], addresses issues related to hygrothermal conditions in churches, with emphasis on air temperature and humidity which periodically exceed the values of thermal comfort for historical buildings and exert a negative impact. Microorganisms present on religious items are responsible for these physical and chemical changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chmiel et al [ 21 ] investigate bacterial and fungal aerosols in ten historical attractions from Kraków (churches, crypts, museums and libraries). Research conducted by Nawalany et al [ 22 ], Stanaszek-Tomal [ 23 ] and Mang et al [ 24 ], addresses issues related to hygrothermal conditions in churches, with emphasis on air temperature and humidity which periodically exceed the values of thermal comfort for historical buildings and exert a negative impact. Microorganisms present on religious items are responsible for these physical and chemical changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of analyzing the influence of location on the energy management of the studied buildings showed that the external climate significantly determined the amount of energy expenditure for heating purposes. Similar relationships were also found in buildings outside the agricultural sector [28,29]. The phenomenon of heat exchange with the ground and the possibility to use the potential of the ground as a specific regulator of the interior microclimate is a very important aspect from a year-round building operation perspective.…”
Section: Discussionmentioning
confidence: 54%
“…Current state of knowledge shows that the share of the ground in the total energy balance of residential and industrial buildings is about 5-10% [17]. As a result of continuous development of digital technologies, numerical methods are increasingly used for modelling and forecasting of physical phenomena [30][31][32]. However, computer simulations have some limitations and do not account for all factors which in reality can affect the studied parameters [23].…”
Section: Discussionmentioning
confidence: 99%